Long-term nitrogen deposition does not exacerbate soil acidification in tropical broadleaf plantations. (8th November 2021) - Huang, Juan; Zhang, Wei; Li, Yuelin; Wang, Senhao; Mao, Jinhua; Mo, Jiangming; Zheng, Mianhai
Abstract: Nitrogen (N) deposition induces soil acidification in natural forests; however, whether it increases soil acidity in tropical plantations with simple tree structures compared with natural forests remains unclear. This study aimed to investigate the effects of N deposition on the soil acidity of tropical broadleaf plantations dominated by Acacia auriculiformis and Eucalyptus urophylla in South China, which has been enduring N deposition for over 30 years, and investigate the reasons for the changes in soil acidity. Long-term N addition did not affect soil acidity in the two plantations, with no significant changes in soil pH values, and exchangeable non-acidic and acidic cation concentrations. Long-term N deposition did not significantly affect the plant and total soil N concentrations, but significantly increased the soil nitrous oxide emission rates and total dissolved N concentrations in the soil solutions. Our findings indicate that most of the added N was lost via leaching and emissions, such that long-term N addition did not exacerbate soil acidification in broadleaf plantations, thereby providing novel insight into the effects of atmospheric N deposition on forest ecosystems. Overall, our study indicates that long-term N deposition does not always lead to soil acidification in tropical forests, as previously expected.